Potential use of fermented plant extracts as biological control agents for citrus mealybugs, Planococcs citri - Khadem, Ahad Gul; Nyuk, Ling Chin; Mokhtar, Anis Syahirah; Wei, Hong Lau (Agri Bio Publishers, 2022)
Management of mealy bugs, Planococcus citri is challenging due to its wide host range, presence of a waxy coating on the body, and high reproductive potentiality. The objective of the present study was to evaluate the insecticidal potential of different fermented plant extracts as potential biological control agents for citrus mealy bugs. The efficacy of the following fermented plant extracts on P. citri was estimated : onion (Alium cepa), garlic (Allium sativum), turmeric (Curcuma longa), aromatic ginger (Kaempferia galanga), lemongrass (Cymbopogon citratus), Mexican mint (Plectranthus amboinicus), variegated mintleaf (Plectranthus madagascariensis), peppermint (Mentha × piperita), kaffir lime (Citrus hystrix) and lime (Citrus aurantiifolia). More than 80% mealy bugs died after 120 h post-treatment with LC50 less than 10% (w/v) resulted by the fermented Mexican mint extract, fermented turmeric extract and fermented onion extract. The mealy bugs wax was detached after being treated with fermented plant extracts at concentrations above 10% (w/v). High phytotoxic (more than 40% leaf damage after 72 h post-treatment) effect was recorded in the fermented Mexican mint extract. These findings were/are considered as the first worldwide report on such interactions. The research findings reported in the present study revealed the potential use of fermented plant extract as biological control agent for P. citri, which will benefit mealy bugs control at a safer and environmentally-friendly approach.